Self-Regulation among Students with Learning Disabilities in English Language and its Relationship to Some Variables (Global Journal of Human-Social Science, 2021)
The present study aimed at identifying the level of self-regulation among students with learning disabilities in English language in Irbid Governorate and its relationship with the variables of gender and school grade The study sample consisted of 380 male and female students in the elementary stage The study used the descriptive approach and developed the self-regulation scale as an instrument to collect data The content validity and reliability of the instrument were ensured using the Cronbach Alpha and repetition methods The results showed that there were statistically significant differences in the level of self-regulation among those with learning disabilities due to the gender variable in favor of males and to the school grade variable in favor of the second primary grade
Keywords: self-regulation; learning difficulties; english language; elementary stage